Guns, laws and public shootings in the United States. Issue 49 (20th October 2016) - Blau, Benjamin M.; Gorry, Devon H.; Wade, Chip
ABSTRACT: Since the late 1990s, there have been increasing numbers of public shootings carried out with firearms in the United States. These tragedies continually renew the regulatory debate concerning public safety while considering civil liberties. Using a unique data set, we investigate whether laws correspond to whether an event occurs and the effects of event-specific characteristics on public shooting outcomes. In particular, we analyse how state-specific gun laws, the types of firearms, the shooting venues and the mental health of the gunman impact the outcomes of public shootings. Results show that most gun laws are unrelated to whether an event occurs. In addition, common state and federal gun laws that outlaw assault weapons are unrelated to the likelihood of an assault weapon being used during a public shooting event. Moreover, results show that the use of assault weapons is not related to more victims or fatalities than other types of guns. However, the use of hand guns, shot guns and high-capacity magazines is directly related to the number of victims and fatalities in a public shooting event. Finally, the gunman's reported mental illness is often associated with an increase in the number of victims and fatalities.